Sistem Informasi Peremajaan Tabung Gas Elpiji PT. Ladang Usaha Bersama Palembang - Damayanti, NIta Rosa (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2017)
In order to facilitate the processing of LPG tube stock data at PT. Ladang Usaha Bersama, it required a software that can process data of damaged gas tubes stock and which have been rejuvenated. Based on these problems then the necessary analysis so that the results can be obtained by found the needs needed for software application data processing stock of LPG gas tube web-based at PT. Ladang Usaha Bersama. Result of problem analysis done before, hence can be designed a data processing software rejuvenation of LPG gas tube using SDLC method. Based on the results of this study can be concluded that this software can assist in processing data of LPG tube rejuvenation stock and can display report required by PT. Ladang Usaha Bersama.Keywords : Application, Stock, Data Processing.